2016
DOI: 10.1097/pcc.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Broad-Spectrum Antimicrobial Use in a Tertiary Children’s Hospital Post Antimicrobial Stewardship Program Guideline Implementation*

Abstract: Guideline implementation was successful in reducing targeted broad-spectrum antibiotic use and acquisition cost. Programs with very limited resources may find similar implementation of guidelines effective to provide initial success, so that putting into practice one of the more resource intensive core strategies, such as prospective audit and feedback, may be feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 6 publications
2
84
0
2
Order By: Relevance
“…In human medicine, antimicrobial use guidelines have been developed and implemented as one of the strategic goals to optimize antimicrobial use (Goldmann et al, 1996), and they have shown to have a positive effect on the antimicrobial prescribing behavior (Smith et al, 2012;Lee et al, 2016). In veterinary medicine, only in a limited number of studies, the impact of antimicrobial guidelines has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, antimicrobial use guidelines have been developed and implemented as one of the strategic goals to optimize antimicrobial use (Goldmann et al, 1996), and they have shown to have a positive effect on the antimicrobial prescribing behavior (Smith et al, 2012;Lee et al, 2016). In veterinary medicine, only in a limited number of studies, the impact of antimicrobial guidelines has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of other similar studies in Singapore, Iran and US in hospitalized children and women showed that the proper prescription of carbapenems using the ASP was increased significantly, also proved that the ASP protocol can be successfully applied to promote quality of care of hospitalized patients (22,25,26).…”
Section: Discussionmentioning
confidence: 66%
“…Other similar studies in Singapore, Iran, and the US in hospitalized children and women showed that the proper prescription of carbapenems using the ASP was increased significantly, also proved that the ASP protocol can be successfully applied to promote quality of care of hospitalized patients (22,25,26).…”
Section: Discussionmentioning
confidence: 67%